LEADERSHIP OF THE HEAD OF A CORRECTIONAL INSTITUTION IN ACHIEVING THE TITLE OF CORRUPTION-FREE AREA (Case study at the Semarang Class II Women's Correctional Institution) - Mulyani Rahayu (Association of Certified Fraud Examiners Indonesia Chapter, 2020)
Prisons in Indonesia are often described as a very terrible place and even there is no good side to be proud of. The case occurred recently has worsen the image of prison,where the head of Kalianda Prison was arrested by the Provincial Narcotics Agency (BNNP) for his involvement in illegal drugs that were traded in prison. This condition is very contrary to the condition at the Semarang Class II Women's Correctional Institution. The success of Semarang Class II Women's Correctional Institution in suppressing illegal levies cannot be separated from the leadership role of the head of the prison. The presence of a leader greatly affects the integrity of employees in his ranks. The Semarang Class II Women's Correctional Institution is the only one of the 611 Correctional Institutions (Technical Implementation Unit) which bears the title of Corruption-Free Area in the Ministry of Law and Human Rights of the Republic of Indonesia. This study aims to describe how the leadership of the Head of Semarang Class II Women's Correctional Institution as a role model in achieving zero illegal levies using qualitative descriptive methods through field observations and in-depth interviews with structural officials, officials and inmates as informants.